Developments and opportunities in fungal strain engineering for the production of novel enzymes and enzyme cocktails for plant biomass degradation - Kun, Roland S.; Gomes, Ana Carolina S. [UNESP]; Hildén, Kristiina S.; Salazar Cerezo, Sonia; Mäkelä, Miia R.; de Vries, Ronald P. (Elsevier, 2019)
Fungal strain engineering is commonly used in many areas of biotechnology, including the production of plant biomass degrading enzymes. Its aim varies from the production of specific enzymes to overall increased enzyme production levels and modification of the composition of the enzyme set that is produced by the fungus. Strain engineering involves a diverse range of methodologies, including classical mutagenesis, genetic engineering and genome editing. In this review, the main approaches for strain engineering of filamentous fungi in the field of plant biomass degradation will be discussed, including recent and not yet implemented methods, such as CRISPR/Cas9 genome editing and adaptive evolution.
Keywords: Adaptive evolution; Chemical mutagenesis; Epigenetics; Genetic engineering; Genome editing; Omics; UV mutagenesis